The effect of bingo-KDK game to improve preservice counselor communication skills - Wahyuni, Fitri; Hidayah, Nur; Ramli, M.; Hutasuhut, Ida Juliana; Hanafi, Husni; Kurniawan, Nanda Alfan; Putri, Suci Nora Julina (Journal of Education and Learning (EduLearn), 2025)
Basic communication skills are primary modalities for the counselor and should be developed from their preservice education. In Indonesia, most guidance and counseling major provide the basic communication skills course as a hybrid course, containing both theoretical and practical learning. This model had many challenges in making a balanced outcome for both the theoretical knowledge and practical skills. This research aims to test the bingo-keterampilan dasar komunikasi (KDK) as an integrated learning strategy of bingo games, reverse role-play, and reflection sessions to improve preservice counselors’ basic communication skills. This research used a quantitative method with a randomized control trial (RCT) experiment design. This research involved 56 preservice counselors, divided randomly into experiment and control groups. The measurement used is the performance test of the basic communication skills course. Data analysis focused on measuring basic statistics and t-tests. The results show the experiment group has higher results and is significantly different from the control group. This effectiveness was supported by the learning atmosphere that indirectly increased the involvement of the preservice counselor. This research suggests exploring the mental experience and performance measurement during the learning sessions using the bingo-KDK game.